HALAL METAVERSE TOURISM: STRATEGY TO CREATE INDONESIA AS THE CENTER FOR ISLAMIC TOURISM IN THE WORLD - Sukmamedian, Haufi; Ilham, Wahyudi (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Tourism in Indonesia is an important economic sector. In this modern era, rapid technological developments have had a major impact on various sectors, including the tourism industry. Apart from being an economic engine, tourism is considered capable of reducing unemployment. In the national economy, tourism is a sector that is expected to increase the country's foreign exchange earnings. Indonesia is listed as the country with the second largest Muslim population in the world after Pakistan, which is expected to become a skilled driver of halal tourism in developing destinations. After the Covid-19 pandemic, tourism in Indonesia declined. Based on a Statista report, the world tourism sector lost 100.8 million jobs in 2020. Asia Pacific was the tourist area most affected by the pandemic, which lost 63.4 million jobs. One effort to restore tourism in Indonesia is by implementing metaverse tourism innovation as an effort to restore the tourism sector post-pandemic, especially to suppress the phenomenon of overtourism. Metaverse technology can help all aspects of life in the economic, educational and business sectors. It is hoped that the use of Metaverse technology can become a strategy to make Indonesia a center for Islamic tourism in the world. This research is qualitative research with a descriptive approach. Researchers use research data in the form of secondary data obtained from a number of credible sources such as scientific articles, books and a number of other sources that are credible and commonly used in research. These data were analyzed using analytical tools with stages of data collection, data selection, data reduction and drawing conclusions. Keywords: Halal Metaverse Tourism, Indonesia, Tourism